Mobilização e participação social no processo de regularização fundiária urbana no município de Luzinópolis - TO - SILVA, Cassilda Figueira da (2022)
The present study aimed to understand the importance of social participation in Urban Land Regularization (REURB) actions in the municipality of Luzinópolis, State of Tocantins, from the perspective of the community, seeking to know the processes and procedures of social mobilization applied to urban land regularization; identify the challenges of social participation and; observe communication processes and dynamics in works involving REURB. And in this way, to understand, together with the community, the relevance of social participation in the process of land regularization. Considering the importance of participatory processes for the democratization of public policies and that, in the case of REURB, it must go through all the stages of execution and continue during the implementation of legal, urban, environmental and social measures that should contribute to the improvement of the population's quality of life resident in the regularization area. As a methodology for the development of the work, a quantitative and qualitative approach was used, with a descriptive character, bibliographic research, field research and direct observation. It was concluded that, to a large extent, the community realized the importance of participating in the actions, as they had the opportunity to give their opinion on measures to improve the quality of life, based on the land regularization project. Noting, however, that further clarification is necessary about the process, for better understanding.